The Improvement of Student Learning Outcomes at SMKN 5 Jember - Yayuk Widhyawati; Muhammad Dimyati; Hary Sulaksono (Universitas Pendidikan Ganesha, 2019)
The quality of education in a school, one of which can be seen from the learning outcomes of its students. Student learning outcomes at SMKN 5 Jember can be measured from four factors, such as: learning environment, teacher competency, learning method and student absorption in receiving lessons. Based on the explanation above, the formulation of the problem in this study is how is the influence of the learning environment, teacher competency, learning methods and student absorption in receiving lessons on student learning outcomes at SMKN 5 Jember. This study aims to examine whether there is an influence of /the learning environment, teacher competence, learning methods and student absorption in receiving lessons on student learning outcomes at SMKN 5 Jember. The population of this study were students of SMKN 5 Jember 2017/2018 academic year. In this study, researchers will use accidental sampling. Accidental sampling is a chance-based sample determination technique, that anyone who happens to meet with a researcher can be used as a sample, if it is seen by someone who happens to be a suitable data source. In this study, researchers took a sample of 30 respondents, because this study uses multiple linear regression analysis SPSS version 16 application. Based on data analysis shows that the learning environment has a significant effect on student learning outcomes at SMKN 5 Jember. Whereas teacher competency, learning method and student absorption in accepting lessons do not give effect to student learning outcomes at SMKN 5 Jember.